2022
DOI: 10.3389/fncel.2021.794675
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Pathway Modulation Normalizes Expression of Olig2 in Rostrally Patterned NPCs With Trisomy 21

Abstract: The intellectual disability found in people with Down syndrome is associated with numerous changes in early brain development, including the proliferation and differentiation of neural progenitor cells (NPCs) and the formation and maintenance of myelin in the brain. To study how early neural precursors are affected by trisomy 21, we differentiated two isogenic lines of induced pluripotent stem cells derived from people with Down syndrome into brain-like and spinal cord-like NPCs and promoted a transition towar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…To assess the influence of variability in individual genome on DEX gene discovery, we repeated the analyses replacing Olmos-Serrano et al, 2016 dataset with Palmer et al, 2021 (all) dataset ( Supplemental Figure 8A-D ). We first observed that Palmer et al, 2021 contained fewer unique HSA21 DEX genes (16 of 111, 14.4%) than Olmos-Serrano et al 2016 (17 of 45, 37.8%), when compared to our dataset and Klein et al, 2022 ( Supplemental Figure 8A ). As expected, most HSA21 DEX genes (95 of 98, 96.9%) from Palmer et al, 2021 (old fem.)…”
Section: Resultsmentioning
confidence: 48%
See 4 more Smart Citations
“…To assess the influence of variability in individual genome on DEX gene discovery, we repeated the analyses replacing Olmos-Serrano et al, 2016 dataset with Palmer et al, 2021 (all) dataset ( Supplemental Figure 8A-D ). We first observed that Palmer et al, 2021 contained fewer unique HSA21 DEX genes (16 of 111, 14.4%) than Olmos-Serrano et al 2016 (17 of 45, 37.8%), when compared to our dataset and Klein et al, 2022 ( Supplemental Figure 8A ). As expected, most HSA21 DEX genes (95 of 98, 96.9%) from Palmer et al, 2021 (old fem.)…”
Section: Resultsmentioning
confidence: 48%
“…We first investigated the DEX genes from each study located on chromosome 21 (HSA21) and found statistically significant overlaps between every pair of datasets with p < 0.001 ( Figure 5A,B ). Particularly, 45 (88%) and 43 (84%) out of the 51 HSA21 DEX genes from our current dataset were also DEX in the Klein et al, 2022 and Palmer et al, 2021 (old fem.) datasets, respectively.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations